VALUE RELEVANCE OF CORPORATE SOCIAL ACCOUNTING REPORTING OF LISTED BANKS IN NIGERIA (Journal of Global Accounting, 2023)
This study investigates the value relevance of corporate social accounting reporting on the market share price (MSP) of listed banks in Nigeria. The study adopts the ex-post facto research design. The sample consisted of eight listed banks on the Nigerian Stock Exchange. The study relied on secondary data; obtained from annual reports for the period 2007 to 2016. The data were analysed using descriptive statistics, Pearson correlation and Robust Least Square (RLS) analysis. The researchers made use of Eview software in the data analysis. The findings revealed that scholarship reporting is statistically significant in influencing market share price (MSP) of listed banks; while,health and safety reporting is not statistically significant in influencing the MSP of listed banks in Nigeria. Based on this, the study recommends that Banks consider improved disclosure of their corporate social services such as scholarship services in their annual reports as this was found to have significant influence on market share price.
Keywords: Value Relevance; Corporate Social Reporting; Scholarship Reporting; Health and Safety Reporting; Market Share Price